(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The levels of lead (Pb), cadmium (Cd), and nickel (Ni) in spinach (Spinacia oleracea), tomato (Lycopersicon esculentum) and cauliflower (Brassica oleracea) and in the rizosphere soils of the industrially polluted (Konabari, Gazipur; Keranigonj, Dhaka), and non-polluted (Bangladesh Agricultural Research Institute-BARI, Gazipur) areas were studied. Four samples from each area were collected during February 2008. Their concentrations varied with the metals and locations, showing the trend: Ni>Pb>Cd and directly polluted> indirectly polluted>non-polluted soils. The order of the elements in spinach, tomato, and cauliflower and their concentration ranges in μg/g of dry weight were Ni (1.265-5.369), (2.031-4.957), (1.698-4.447); Pd (0.767-1.440), (1.027-1.968), (0.486-1.119); and Cd (0.559-1.40), (0.630-1.303), (0.506-0.782), respectively. Similarly, the order of the elements in rizosphere soils of spinach, tomato, and cauliflower and their concentration ranges in μg/g of dry weight were Ni (12.29-31.52), (13.67-31.98), (14.20-34.34); Pd (3.560-7.980), (3.900-8.447), (3.718-7.337); and Cd (1.473-3.760), (1.553-3.833), (1.640-3.670), respectively. Lead concentration was higher in tomato, followed by spinach and the least in cauliflower irrespective of the location. Cadmium and Ni concentration were found in the order of spinach>tomato>cauliflower, especially in the industrially polluted areas. Concentrations of metals in vegetable samples were related to their concentration in the corresponding soils. Lead, Cd, and Ni concentrations in the studied vegetables were higher than those found in vegetables from other countries, but they were lower than the maximum level allowed in India. Metal transfer factors from soil to vegetables are found to be significant for Cd, Pb and Ni. Key Words: Cadmium; lead; nickel; polluted soils; vegetables. DOI: 10.3329/bjar.v34i4.5831 Bangladesh J. Agril. Res. 34(4) : 545-554, December 2009